Pengembangan Aplikasi Live Chat Menggunakan Extreme Programing - Permana, Edwar; Sutedi, Ade; Elsen , Rickard (Jurnal Algoritma, 2024)
Reservations are a form of service provided by companies for arranging or ordering, for example, tickets, tables, hotel rooms for someone at a certain time. There are many ways to provide reservation services, one of which is through communication media. This research is a development of "Designing a Reservation Application for Karunia Tour and Travel Services with Payment Gateway Implementation". The aim is to complete the reservation application with a real-time chat service feature (livechat) to help companies and consumers communicate regarding tour and travel reservation services. Methodology The application development used in this research is Extreme Programing (XP) which is divided into four stages including Planning, Design, Coding and Testing. The application design model uses Unified Modeling Language (UML) and Class Responsibility Collaboration (CRC). chat that is integrated with the tour and travel reservation application at the Jasa Karunia company.